Using comprehensive geriatric assessment for quality improvements in healthcare of older people in UK care homes: protocol for realist review within Proactive Healthcare of Older People in Care Homes (PEACH) study - Zubair, Maria; Chadborn, Neil; Gladman, John R.F.; Dening, Tom; Gordon, Adam L.; Goodman, Claire (BMJ Publishing Group Ltd, 2017)
Introduction